Quantum squeezing and entanglement from a two-mode phase-sensitive amplifier via four-wave mixing in rubidium vapor - Yami Fang; Jietai Jing (New Journal of Physics, 2015)
Phase-sensitive amplifiers (PSAs) have been widely studied in fiber amplifiers, with remarkable recent advances. They have also been implemented in an SU(1,1) interferometer. In this paper, we study an experimental scheme for the implementation of a two-mode PSA based on a four-wave mixing process in rubidium vapor. With the process seeded by coherent probe and conjugate beams, quantum correlation including intensity difference/sum squeezing and quadrature entanglement between the output probe and conjugate fields are theoretically analyzed. Compared to previous related research, several new and interesting results are reported here. The maximal degree of intensity difference squeezing can be enhanced by nearly 3 dB compared to a phase-insensitive amplifier with the same gain. It is also possible to generate intensity sum squeezing between the probe and conjugate fields by choosing the specific phase of the input beams. Moreover, quadrature entanglement between the probe and conjugate beams, which can be manipulated by the phase of the input beams, is predicted. Our scheme may find a variety of applications in quantum metrology and quantum information processing owing to its ability of quantum squeezing and entanglement manipulation.